Evidence in Favor of an Alternative Glucocorticoid Synthesis Pathway During Acute Experimental Chagas Disease - da Silva Oliveira Barbosa, Esdras; Roggero, Eduardo A.; González, Florencia B.; Fernández, Rocío del Valle; Carvalho, Vinicius Frias; Bottasso, Oscar A.; Pérez, Ana R.; Villar, Silvina R. (Frontiers in Endocrinology, 2020)
It is well-established that infectious stress activates the hypothalamus–pituitary–adrenal axis leading to the production of pituitary adrenocorticotropin (ACTH) and adrenal glucocorticoids (GCs). Usually, GC synthesis is mediated by protein kinase A (PKA) signaling pathway triggered by ACTH. We previously demonstrated that acute murine Chagas disease courses with a marked increase of GC, with some data suggesting that GC synthesis may be ACTH-dissociated in the late phase of this parasitic infection. Alternative pathways of GC synthesis have been reported in sepsis or mental diseases, in which interleukin (IL)-1β, prostaglandin E2 (PGE2), and/or cAMP-activated guanine nucleotide exchange factor 2 (EPAC2) are likely to play a role in this regard. Accordingly, we have searched for the existence of an ACTH-independent pathway in an experimental model of a major parasitic disease like Chagas disease, in addition to characterizing potential alternative pathways of GC synthesis. To this end, C57BL/6 male mice were infected with T. cruzi (Tc), and evaluated throughout the acute phase for several parameters, including the kinetic of GC and ACTH release, the adrenal level of MC2R (ACTH receptor) expression, the p-PKA/PKA ratio as ACTH-dependent mechanism of signal transduction, as well as adrenal expression of IL-1β and its receptor, EPAC2 and PGE2 synthase. Our results reveal the existence of two phases involved in GC synthesis during Tc infection in mice, an initial one dealing with the well-known ACTH-dependent pathway, followed by a further ACTH-hyporesponsive phase. Furthermore, inflamed adrenal microenvironment may tune the production of intracellular mediators that also operate upon GC synthesis, like PGE2 synthase and EPAC2, as emerging driving forces for GC production in the advanced course of Tc infection. In essence, GC production seems to be associated with a biphasic action of PGE2, suggesting that the effect of PGE2/cAMP in the ACTH-independent second phase may be mediated by EPAC2.